APLIKASI ARANG KOMPOS PADA ANAKAN TUSAM - Sri Komarayati; Gusmailina Gusmailina; G Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Compost charcoal is a compounded stuff of charcoal and compost, which is produced by composting process. The compost charcoal compound products is a new break through in the composting techniques as an attempt to improve the qualitiy of compost.This experiment dealt with the application of compost and compost charcoal to the Pinus merkusii seedling, in the greenhouse for 3 months period.The results revealed that the use of compost alone 30 % of total media weight could stimulate the growth of Pinus merkusii seedlings to the level of 1 time higher in height ; 7 times greater in diameter ; 1,5 times longer in roots length, and 1,5 times heavier biomass in the dry weight than those of control (i.e. seedlings without compost treatment). Comparatively, the corresponding figures in the use of compost charcoal compound also at 30 % were consecutively 1 time higher in height ; 2 times greater in diameter; 1,5 2,6 times longer in root length and 4,6 6,0 times heavier biomass than the control.The use of compost and charcoal compost both at 30 % of total media weight showed the best effects on the growth of Pinus merkusii seedlings.